Enalapril alters the formation of the collagen matrix in spontaneously hypertensive rats - Bomfim,Alfredo de Souza (2003)
OBJECTIVE: To assess the effect of the inhibition of the angiotensin-converting enzyme on the collagen matrix (CM) of the heart of newborn spontaneously hypertensive rats (SHR) during embryonic development. METHODS: The study comprised the 2 following groups of SHR (n=5 each): treated group - rats conceived from SHR females treated with enalapril maleate (15 mg. kg-1.day-1) during gestation; and nontreated group - offspring of nontreated females. The newborns were euthanized within the first 24 hours after birth and their hearts were removed and processed for histological study. Three fields per animal were considered for computer-assisted digital analysis and determination of the volume densities (Vv) of the nuclei and CM. The images were segmented with the aid of Image Pro Plus® 4.5.029 software (Media Cybernetics). RESULTS: No difference was observed between the treated and nontreated groups in regard to body mass, cardiac mass, and the relation between cardiac and body mass. A significant reduction in the Vv[matrix] and a concomitant increase in the Vv[nuclei] were observed in the treated group as compared with those in the nontreated group. CONCLUSION: The treatment with enalapril of hypertensive rats during pregnancy alters the collagen content and structure of the myocardium of newborns.